Endothelial cell dysfunction and cardiac hypertrophy in the STOX1 model of preeclampsia (2016)
Preeclampsia is a disease of pregnancy involving systemic endothelial dysfunction. However, cardiovascular consequences of preeclampsia are difficult to analyze in humans. The objective of the present study is to evaluate the cardiovascular dysfunction induced by preeclampsia by examining the endothelium of mice suffering of severe preeclampsia induced by STOX1 overexpression. Using Next Generation Sequencing on endothelial cells of mice carrying either transgenic or control embryos, we discovered significant alterations of gene networks involved in inflammation, cell cycle, and cardiac hypertrophy. In addition, the heart of the preeclamptic mice revealed cardiac hypertrophy associated with histological anomalies. Bioinformatics comparison of the networks of modified genes in the endothelial cells of the preeclamptic mice and HUVECs exposed to plasma from preeclamptic women identified striking similarities. The cardiovascular alterations in the pregnant mice are comparable to those endured by the cardiovascular system of preeclamptic women. The STOX1 mice could help to better understand the endothelial dysfunction in the context of preeclampsia, and guide the search for efficient therapies able to protect the maternal endothelium during the disease and its aftermath.